Analisis Kinerja Keuangan dalam Pengelolaan Alokasi Dana Desa Berdasarkan Rasio Efektivitas, Rasio Pertumbuhan, dan Rasio Efisiensi pada Pemerintahan Desa Ranggung Kabupaten Bangka Selatan - Sudirman; Nana Adriana; Jufri Sani Akbar (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2026)
This study analyzes financial performance in the management of Village Fund Allocation (ADD) using the effectiveness ratio, efficiency ratio, and growth ratio. The combination of these three ratios provides a comprehensive perspective for evaluating how the village fund allocation in Ranggung Village is managed to support development and community empowerment goals. The purpose of this research is to evaluate the financial performance of Village Fund Allocation management in Ranggung Village, South Bangka Regency. This study employs a descriptive quantitative method with a financial ratio analysis approach based on documentary data from the Budget Realization Report of Village Revenue and Expenditure (APBDes) of Ranggung Village for the 2021–2024 period. The analysis results show that the financial performance of the Village Fund Allocation (ADD) management in Ranggung Village is classified as good in terms of effectiveness and efficiency, but the financial growth performance remains low. Based on these findings, it is recommended that the Ranggung Village Government improve the organization and filing of financial reports, strengthen efforts to increase village revenue, and optimize overall financial management. Future studies are suggested to include additional financial ratios and expand the scope of analysis to allow for more comprehensive comparisons.